Changes in the traffic situation on city roads after traffic diversion outside the city - Mondek, Norbert; Bulíček, Josef (Scientific Research Center Ltd., 2018)
Road bypasses are constructed to mitigate traffic congestions in city areas. City roads are released and used by city and target traffic (with origin or destination in the city) primary. Travel time can be shortened for all. Question is how journeys within the city area will employ the infrastructure (city roads) originally used for diverted transit traffic. The aim of the article is to find out and to describe the impacts of traffic diversion in dependence on city size and importance of the city. Individual as well as public transport will be assessed, because bypassing has a different impact on each of them. Rerouting of a part of target journeys can be caused by bypassing in individual transport as well. Public transport service can be reduced with the aim to make connections (buses) transiting here faster. Research will be based on evaluation of a set of specific locations (bypassed cities).
Změny dopravní situace na pozemních komunikacích ve městech po odklonění dopravy mimo města
Keywords: city bypass; road transport; traffic diversion; traffic flow; obchvat města; silniční doprava; odklon dopravy; dopravní proud